2017
DOI: 10.1590/1517-869220172303151688
|View full text |Cite
|
Sign up to set email alerts
|

Efeitos dos anabolizantes sobre a densidade de neurônios dos núcleos da base

Abstract: RESUMOObjetivos: Pouco se sabe sobre a atuação dos esteroides androgênicos anabolizantes (EAA) no cé-rebro humano e, por isso, resolvemos estudar a perda neuronal causada pelo uso e abuso de EAA em camundongos. Métodos

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 21 publications
0
7
0
2
Order By: Relevance
“…These data combined suggest that AAS use during adolescence can lead to behavioral effects more pronounced and lasting than in adults [11,12]. Different researchers also indicate that AAS use increases the chances of neuron death in different brain regions in mice [13,14,15].…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…These data combined suggest that AAS use during adolescence can lead to behavioral effects more pronounced and lasting than in adults [11,12]. Different researchers also indicate that AAS use increases the chances of neuron death in different brain regions in mice [13,14,15].…”
Section: Introductionmentioning
confidence: 87%
“…Encephalon fragments were processed following standardized histological procedure [13,15]. To estimate the neuron density, simple random sampling method was used [22,23,24,25].…”
Section: Methodsmentioning
confidence: 99%
“…These results are in agreement with previously published outcomes. 28,29 In general, it seems that AAS physiological doses have the ability to play a neuroprotective role; however, when AAS is administered in high concentrations, they appear to exert a deleterious effect on neuron body cells, and most studies show an excitotoxic effect when using concentrations. The same was observed by some other authors, who found that pre-treatment with high doses of testosterone increased Nmethyl-D-aspartate (NMDA) toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…The treatment consisted in application of two anabolic steroids, the first, nandrolone decanoate marketed under the name Deca Durabolin® and the second an association of testosterone propionate, testosterone fenpropionate, testosterone isocaproate and testosterone decanoate marketed under the name of Durateston ®. The animals were treated for one (1) month, the doses of 0.02 ml physiological solution being that of Durateston® 83.3 mg / kg (0.02 ml) and the doses of Deca Durabolin® 16.6 mg / kg (0.02 ml) applied once a week [14][15][16][17][18].…”
Section: Methodsmentioning
confidence: 99%